KONSEP ‘URF DALAM PANDANGAN ULAMA USHUL FIQH (TELA’AH HISTORIS) - Harun, Muhamad; Fauziah, Fauziah (Nurani, 2014)
Abstract: Historically, the building of Islamic law shows a decision of law of a new case (nazilah). This decision is not absolute based on al-Qur’an or hadis, but it is based on this condition itself. Ijtihad happened not only after Rasullah’s era, even it also happened in Rasullah’s era. One of the instruments of istinbath of law in ijtihas is ‘uruf. The discussion of ‘uruf seems interesting to be discussed if it is faced toward question, when the ‘uruf actually exists either structurally or in the form of con-create concept. In other words, “ which group that formulates ‘urf concept becomes a theory of istinbath of law. Even though this paper is a new start of research, but it tries to find the answers by using historical approach.   ملخص: فىالتارخ حفظ الآحكام الإسلاميه تظهر نتجةالكم حول مسئلة حديثة (نز يلة) ليس فقط يعتمد على نص القرآن أو الحديث مطلقاولكنيعتمد على هذاالواقع، الإجتهاد لايقعفقط بعد وفاته صلىالله عليه وسلم بل أثناء حياته نفسه، ومن عثاصرالإستنباط الحكم فىالإجتهاد هىالعرف، الحوارعن العرف يزداد جذياكم اعتقده الكاتب إذاوجه أمام السؤل متى وجودالعرف سواء كان نظماأم منهاجا واقعيا. يالعبارة الآخرى: اى فرقة التى تجعل نظرية العرف تكون نظرية استنباط الحكم، هذه الرسالة مهماالبحث الآ ول يجرب للبحث عن جواب ياستخد ام تقريب التاريخ.Kata Kunci: ‘Urf, Ushul Fiqh